Perinatal out come of Breech Presentation in the Presentation in the Pretext Mode of Delivery - Alnakash, Abdulrazak H. (AL-Kindy College Medical Journal, 2007)
Objectives: To choose the best mode of deliveryfor term, frank or complete, breech presentationthrough studying the perinatal outcome of each mode ofdelivery decided when managing a group of pregnantladies presented with breech delivery in our centre.Methods: One hundred and fifty pregnant ladiespresented at term with singleton, frank or complete,breech presentation for delivery in our centre during theperiod from May 2004 toAugust 2005.Mode of delivery, parity, gestational age, maternal age,maternal medical illness, and birth weight where thevariables that have been tested in each deliveryincluded in the study to verify their relationship toperinatal outcome.Results: No significant relationship is foundbetween the occurrence of adverse perinatal outcomeand the variables. However, mode of delivery was themajor determinant of the perinatal outcome.of the 150 pregnant ladies, 46 were delivered vaginally,32 had elective caesarean section, and the remaining 54pregnant, had undergone an emergency caesarean sectionbecause they were presented with labour. Thirteen (8.6%) babies were adversely affected by the process ofdelivery, 9 (5%) of them were delivered by vaginal route,3 (2 %) delivered by emergency caesarean section and one(0.6%) by elective caesarean section.Conclusion: Elective caesarean section is regardedthe safest way of delivery for those with term, frank orcomplete, breech presentation.